Perspectivas psicanalíticas sobre saúde mental na graduação e a exploração de identidades fora dos binarismos de gênero - Souza, Vi Pereira de (Universidade Federal de São Carlos, 2023)
Taking Psychoanalysis as an interesting method for investigating subjectivity, the present study aimed to understand—not only the trajectories within the institution and the use of affirmative policies—but also certain dimensions of the exploration of identities that deviate from pre-established notions of gender among undergraduate students. Narrative interviews were conducted using the method of free association to access unconscious material, drawing on Klein’s and Winnicott’s theoretical frameworks regarding object relations and how these relate to the individual’s self-understanding and sense of identity.The study focused on undergraduate students, considering their high psychosocial vulnerability to psychological distress—especially those belonging to social minorities—as well as their significant representation within the non-binary population. The results indicated that public universities were perceived as safer environments for exploring identities outside gender binarisms, compared to other contexts, confirming the study’s main hypothesis. Finding a community greatly supported the development of healthier relationships with one’s own identity, reducing internalized anxieties and allowing for greater security in self-identification. Participants reported negative episodes involving the use of their chosen names; however, in general, they felt included by the affirmative policies they accessed. The study highlights the need for awareness and training among professors—who were primarily involved in the negative experiences—as well as the importance of effective institutional reporting mechanisms against discrimination.
Psychoanalytic perspectives on mental health in undergraduate studies and the exploration of identities outside of gender binaries
Keywords: Não binário; Gênero; Estudantes de graduação; Universidade; Psicanálise; Associação Livre; CIENCIAS HUMANAS::PSICOLOGIA; 5. Igualdade de Gênero